Microsatellite instability-high in stage IV colorectal cancer: prevalence, and clinicopathological characteristics in Malaysia - Izhar, Nur Amira; Sainal, Mohd Yusof; Mohamad Salmi, Muhammad Irfan; Elagili, Faisal; Md Nor, Azmi (John Wiley & Sons, 2024)
Aim: The purpose of this study was to estimate the prevalence of Microsatellite Instability High (MSI-H) in stage IV colorectal cancer in Malaysians and to describe MSI-H clinicopathological characteristics. Method: All patients with stage IV colorectal cancer who underwent surgical resection of the primary tumor between January 2017 and December 2020 were included in the single-center retrospective study. MSI status was determined. Clinicopathological features were evaluated. Results: Among 42 patients with stage IV colorectal cancer, 4 patients (10%) had MSI-H (57% were men) with an average age of 58 ± 21 years and were related to left-sided colonic origin, adenocarcinoma, moderately differentiated, lymphovascular invasion, single-organ metastasis, peritoneal metastasis, and Malay race. The average survival durations for MSI-H and Microsatellite Stable (MSS) were 15 ± 14 and 18 ± 16 months, respectively (p= 0.77). Conclusion: In this study, MSI-H was detected in 10% of individuals with stage IV colorectal cancer. However, our data highlight the features and prognostic relevance of MSI-H in Malaysian stage IV colorectal cancer patients.